Software Infrastructure and Tools for the TRIPS Prototype - Yoder, Bill; Burrill, Jim; McDonald, Robert; Bush, Kevin; Coons, Katie; Gebhart, Mark; Govindan, S.; Maher, Bert; Nagarajan, Ramadass; Robatmili, B.; Sankaralingam, Karthikeyan; Sharif, Sadia; et al. (3rd Annual Workshop on Modeling, Benchmarking and Simulation (MoBS), 2007)
The TRIPS hardware prototype is the first instantiation of an Explicit Data Graph Execution (EDGE) architecture. Building the compiler, toolset, and system software for the prototype required supporting the system’s unique dataflow construction, its banked register and memory configurations, and its novel Instruction Set Architecture. In particular, the TRIPS ISA includes (i) a block atomic execution model, (ii) explicit mappings of instructions to execution units, and (iii) predicated instructions which may or may not fire, depending on the outcome of preceding instructions. Our primary goal has been to construct tools to consume standard C and Fortran source code and generate binaries both for the TRIPS software simulators and hardware proto- type. A secondary goal has been to build the software infrastructure on standard platforms using standard tools. These goals have been met through a combination of off-the-shelf and custom tools. We present a number of design issues and their resolution in enabling end users to exercise the prototype ISA using familiar tools and programming interfaces. Finally, we offer download instructions for those who wish to test-drive the TRIPS tools.